Association Between Neighborhood-Level Socioeconomic Disadvantage and Patient-Reported Outcomes in Lumbar Spine Surgery. Issue 1 (25th January 2023) - Zhang, Justin K.; Greenberg, Jacob K.; Javeed, Saad; Khalifeh, Jawad M.; Dibble, Christopher F.; Park, Yikyung; Jain, Deeptee; Buchowski, Jacob M.; Dorward, Ian; Santiago, Paul; Molina, Camilo; Pennicooke, Brenton H.; et al.
Abstract : Abstract : BACKGROUND: Despite an increased understanding of the impact of socioeconomic status on neurosurgical outcomes, the impact of neighborhood-level social determinants on lumbar spine surgery patient-reported outcomes remains unknown. OBJECTIVE: To evaluate the impact of geographic social deprivation on physical and mental health of lumbar surgery patients. METHODS: A single-center retrospective cohort study analyzing patients undergoing lumbar surgery for degenerative disease from 2015 to 2018 was performed. Surgeries were categorized as decompression only or decompression with fusion. The area deprivation index was used to define social deprivation. Study outcomes included preoperative and change in Patient-Reported Outcomes Measurement (PROMIS) physical function (PF), pain interference (PI), depression, and anxiety (mean follow-up: 43.3 weeks). Multivariable imputation was performed for missing data. One-way analysis of variance and multivariable linear regression were used to evaluate the association between area deprivation index and PROMIS scores. RESULTS: In our cohort of 2010 patients, those with the greatest social deprivation had significantly worse mean preoperative PROMIS scores compared with the least-deprived cohort (mean difference [95% CI]—PF: −2.5 [−3.7 to −1.4]; PI: 3.0 [2.0-4.1]; depression: 5.5 [3.4-7.5]; anxiety: 6.0 [3.8-8.2], all P < .001), without significant differences in change in these domains at latest follow-up (PF: +0.5 [−1.2 to 2.2]; PI: −0.2 [−1.7 to 2.1]; depression: −2 [−4.0 to 0.1]; anxiety: −2.6 [−4.9 to 0.4], all P > .05). CONCLUSION: Lumbar spine surgery patients with greater social deprivation present with worse preoperative physical and mental health but experience comparable benefit from surgery than patients with less deprivation, emphasizing the need to further understand social and health factors that may affect both disease severity and access to care.